Finding a safe space for learning and exploration: A qualitative study of recently diagnosed men's experiences of peer support for HIV in Sweden. - Arielle N'Diaye; Tobias Herder; Anette Agardh (PLoS ONE)
In Sweden men account for most new HIV cases, and little is known about the peer support needs of people living with HIV in Sweden. This qualitative study explored how recently diagnosed men perceive and experience peer support in Sweden. Purposively sampled from HIV patient organizations and infectious disease clinics throughout Sweden, data was collected through in-depth individual interviews with 10 men living with HIV, who have experience participating in peer support. Latent and manifest qualitative content analysis produced the overarching theme of Finding a safe space for learning and exploration. Participants used peer support to access key information and skills and as a space to safely explore life with HIV. Participants perceived successful peer support as having the right peer while also receiving support at the right location. Study recommendations include further research on how a peer is defined within the U = U era, further research on the peer support needs of young adults, and further research on the accessibility of peer support.